The ability of cover crops to reduce nitrogen and phosphorus losses from arable land in southern Scandinavia and Finland - Aronsson, H.; Hansen, E. M.; Thomsen, I. K.; Liu, J.; Ogaard, A. F.; Känkänen, H.; Ulen, B. (Soil Water Conservation Soc., 2016)
This review summarizes current knowledge from the literature and experimental studies on the role of cover crops (CCs) in reducing nitrogen (N) leaching and phosphorus (P) losses to waters under the marine and humid continental climate conditions of southern Scandinavia and Finland. Field leaching studies from 11 sites indicate that undersown ryegrass (Lolium spp.) CCs are robust, with average N uptake in aboveground CC biomass of 7 to 38 kg N ha(-1) (6.2 to 34 lb N ac(-1)). Use of CCs sown at harvest (e.g., crucifers) is restricted to southern Scandinavia for climate reasons. The mean relative reduction in N leaching reported for all CCs investigated was 43%, but it ranged between 62% increase instead of a reduction after a red clover (Trifolium pratense) CC on a clay soil to a reduction of 85% to 89% with a perennial ryegrass CC on sandy soils in Denmark (36 to 51 kg ha(-1) [32 to 46 lb ac(-1)]). The data indicate that CCs do not substantially reduce total P losses by runoff and leaching. The effects of CCs on total P leaching varied between a relative increase of 86% and a decrease of 43%. Climate conditions involving freezing-thawing during winter increased the risk of losses of dissolved P from CC biomass. CCs have been implemented to varying degrees into agri-environmental programs. They are mandatory in Denmark and subsidized in Norway, Sweden, and Finland. CCs are grown on 8% of arable land in Denmark, 5% in Sweden, 1% in Finland, and 0.5% in Norway, but CC area is now increasing dramatically in Finland due to a new subsidy program. In all countries there is a need, and potential, for increased use of CCs, but there are several constraints, particularly reduced interest among farmers. There is a clear need to identify CC systems and develop implementation strategies for appropriate distribution of CCs on different soils and regions with respect to required reductions in N leaching and P losses. For this, more knowledge is required, especially about the effect of CCs on P losses (e.g., the effect of species with different partitioning between shoot and root biomass and the effects of CC systems with harvesting of biomass). There is also a need to devise balanced solutions for maintaining and increasing the frequency of CCs in crop rotations to exploit the possible benefits of CCs in reducing nutrient losses.
Keywords: cover crop species; nitrogen leaching; perennial ryegrass; phosphorus leaching; phosphorus surface runoff